Role of Pneumography and Esophageal pH Monitoring in the Evaluation of Infants With Apparent Life-Threatening Event: A Prospective Observational Study. (April 2013) - Mittal, Manoj K.; Donda, Keyur; Baren, Jill M.
Objective . To determine if a positive result on pneumography, diagnosis of gastroesophageal reflux disease (GERD), or nontreatment of those diagnosed with GERD with antireflux medications predicts an increased recurrence risk of apparent life-threatening event (ALTE) over the first 4 weeks of follow-up. Methods . Secondary analysis of a prospective, observational study of 300 infants diagnosed with ALTE. Results . The relative risk of recurrent ALTE was 1.26 (95% confidence interval = 0.47-3.38) among infants with an abnormal versus normal result on pneumography, 1.98 (1.02-3.86) among those diagnosed with GERD versus those not, and 0.46 (0.20-1.03) among those with GERD and started on antireflux medications versus those not started on such medications. Conclusions . Positive pneumography for apnea or reflux does not predict an increase in recurrence rate of an ALTE. Infants diagnosed with GERD are more likely to have recurrent ALTE; treatment with antireflux medications may reduce this risk.